Population Dynamics of Yeasts and Lactic Acid Bacteria (LAB) During Tempeh Production - . EFRIWATI; ANTONIUS SUWANTO; GAYUH RAHAYU; LILIS NURAIDA (Bogor Agricultural University, Indonesia, 2013)
Yeasts and lactic acid bacteria (LAB) are commonly found in tempeh and has been studied separately. However, comprehensive study on population dynamics of yeasts and LAB during tempeh production, including the effect of the difference tempeh production methods has not been reported. This research was aimed in studying the effect of different methods of tempeh production applied in tempeh home industry on the dynamics of yeast and LAB communities. Population dynamics was expressed as both changes of colony number and its phylotype. Samples were obtained from five stages and from two different methods of tempeh production. Observations were carried out employing colony counting on selective media followed by Terminal Restriction Fragment Length Polymorphism (T-RFLP). The study indicated that the population of yeasts and LAB during tempeh production were dynamic and different between these methods. Tempeh production methods affected the presence of yeasts and LAB population as indicated by difference in colony number, the number and diversity of phylotype, as well as number of specific phylotypes grew on plates.